Direct Speaker Gaze Promotes Trust in Truth-Ambiguous Statements - Kreysa, Helene (PLoS One, 2016)
A speaker’s gaze behaviour can provide perceivers with a multitude of cues which are relevant for communication, thus constituting an important non-verbal interaction channel. The present study investigated whether direct eye gaze of a speaker affects the likelihood of listeners believing truth-ambiguous statements. Participants were presented with videos in which a speaker produced such statements with either direct or averted gaze. The statements were selected through a rating study to ensure that participants were unlikely to know a-priori whether they were true or not (e.g., “sniffer dogs cannot smell the difference between identical twins”). Participants indicated in a forced-choice task whether or not they believed each statement. We found that participants were more likely to believe statements by a speaker looking at them directly, compared to a speaker with averted gaze. Moreover, when participants disagreed with a statement, they were slower to do so when the statement was uttered with direct (compared to averted) gaze, suggesting that the process of rejecting a statement as untrue may be inhibited when that statement is accompanied by direct gaze.